2009
DOI: 10.1099/mic.0.022764-0
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the quorum-sensing hierarchy in Pseudomonas aeruginosa: the transcriptional regulator RhlR regulates LasR-specific factors

Abstract: Pseudomonas aeruginosa uses the two major quorum-sensing (QS) regulatory systems las and rhl to modulate the expression of many of its virulence factors. The las system is considered to stand at the top of the QS hierarchy. However, some virulence factors such as pyocyanin have been reported to still be produced in lasR mutants under certain conditions. Interestingly, such mutants arise spontaneously under various conditions, including in the airways of cystic fibrosis patients. Using transcriptional lacZ repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
224
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(255 citation statements)
references
References 89 publications
(112 reference statements)
22
224
2
2
Order By: Relevance
“…6), suggesting that during anaerobic growth, PAI-2-mediated QS may play a more important role than QS induced by the action of other signaling molecules. It was recently reported that PAI-2 production, albeit delayed, still occurs in a lasR mutant strain and that the RhlI/R QS system can override, at least in part, the effects of lasR mutations (13). In addition, comprehensive chronological genetic analysis using a large number of CF isolates revealed that isolates that lost the ability to produce PAI-1 appeared earlier than strains that were unable to produce both PAI-1 and PAI-2 (2).…”
Section: Discussionmentioning
confidence: 99%
“…6), suggesting that during anaerobic growth, PAI-2-mediated QS may play a more important role than QS induced by the action of other signaling molecules. It was recently reported that PAI-2 production, albeit delayed, still occurs in a lasR mutant strain and that the RhlI/R QS system can override, at least in part, the effects of lasR mutations (13). In addition, comprehensive chronological genetic analysis using a large number of CF isolates revealed that isolates that lost the ability to produce PAI-1 appeared earlier than strains that were unable to produce both PAI-1 and PAI-2 (2).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of the LasI-generated signal to a signal synthesis mutant only induced expression by 1.6-fold, but addition of both acyl-HSL signals induced expression by ninefold (Schuster et al, 2003). Thus, it was conceivable that lasR affected dipeptide transport and processing mainly indirectly, through its effect on the rhl system, although this regulation is nutritionally conditional (Medina et al, 2003;Dekimpe and Deziel, 2009;Mellbye and Schuster, 2014). To investigate a possible link between QS and dipeptide metabolism in our experimental system, we quantified the transcript levels of dppA3 and mdpA during growth in CAA medium for our set of eight P. aeruginosa strains used in the previous sections.…”
Section: Transcriptional Regulation Of Dipeptide Transport and Procesmentioning
confidence: 99%
“…LasR and RhlR, in complex with their respective acyl-HSL signals, control the expression of over 300 genes (Hentzer et al, 2003;Schuster et al, 2003;Wagner et al, 2003). The las system controls activation of the rhl system (Latifi et al, 1996;Pesci et al, 1997), but this regulatory hierarchy is nutritionally conditional (Medina et al, 2003;Dekimpe and Deziel, 2009).…”
Section: Introductionmentioning
confidence: 99%